Stalking the Ghost Bird : The Elusive Ivory-Billed Woodpecker in Louisiana - Steinberg, Michael K., 1965- (Book collections on Project MUSE., 2008)
Unseen for more than sixty years and thought to be extinct, interest in the Ivory-Billed Woodpecker exploded in 2004 when two birders reported capturing the bird on film while searching a bottomland forest in Arkansas. STAKING THE GHOST BIRD examines the lengthy debate over the ivory-bill's status by examining the reported sightings and extensive efforts to find the rare bird in Louisiana. In this absorbing study, author Steinberg turns his lifelong interest in the majestic ivory-billed woodpecker into a tale that encapsulates both the mystery and intrigue surrounding the legendary bird.